COMPATIBILIZING EFFECT OF A POLY(ESTER IMIDE) ON THE PROPERTIES OF THE BLENDS OF POLY(ETHER IMIDE) AND A THERMOTROPIC LIQUID-CRYSTALLINE POLYMER .2. MORPHOLOGY AND MECHANICAL-PROPERTIES OF THE IN-SITU COMPOSITE SYSTEM - SEO, YS; HONG, SM; HWANG, SS; PARK, TS; KIM, KU; LEE, S; LEE, J (BUTTERWORTH-HEINEMANN LTD, 1995)
Blends of a thermotropic liquid crystalline polymer (TLCP), [poly(ester amide), PEA, Vectra B950 from Hoechst Celanese] and poly(ether imide) (PEI, Ultem 1000 from G.E.) with the compatibilizer [poly(ester imide), PEsI] were extruded in a twin-screw extruder. The extruded strands were evaluated in terms of morphology and mechanical properties. The morphology of the compatibilized in situ composites was found to be significantly dependent on the concentration of the compatibilizer in the blend. For a TLCP phase content of 25 phr, a maximum reduction in phase size was observed when 1.5 phr by weight of compatibilizer was added to the blend. Al high concentrations of the compatibilizer, flocculation of the TLCP phase was observed. Measurement of the tensile properties shows increased elongation as well as enhanced modulus and strength when properly compatibilized This improvement is ascribed to better adhesion between the TLCP fibrils and the PEI matrix and better dispersion of the TLCP fibrils. Synthesized PEsI significantly improved the adhesion between the matrix phase (PEI) and fibril phase (PEA). However, maxima in tensile modulus, tensile strength and elongation were observed when excess compatibilizer was added. An emulsifying effect of the compatibilizer to coalesce the fibrils is believed to be the cause of the maxima in the tensile properties. Impact strength was seriously increased with the compatibilizer. A maximum in impact strength was also observed, but all compatibilized samples exhibited a higher impact strength than the non-compatibilized one. The reason is believed to be the failure mode difference between the tensile properties and the impact strength.
Keywords: INSITU COMPOSITES; ADHESION; MATRIX; POLYETHERIMIDE; POLYESTER; FIBERS